Heterotrimeric guanosine triphosphate‐binding protein‐coupled modulatory actions of motilin on K+ channels and postsynaptic γ‐aminobutyric acid receptors in mouse medial vestibular nuclear neurons. Issue 3 (9th November 2012) - Todaka, Hiroshi; Tatsukawa, Tetsuya; Hashikawa, Tsutomu; Yanagawa, Yuchio; Shibuki, Katsuei; Nagao, Soichi
Abstract Some central nervous system neurons express receptors of gastrointestinal hormones, but their pharmacological actions are not well known. Previous anatomical and unit recording studies suggest that a group of cerebellar Purkinje cells express motilin receptors, and motilin depresses the spike discharges of vestibular nuclear neurons that receive direct cerebellar inhibition in rats or rabbits. Here, by the slice‐patch recording method, we examined the pharmacological actions of motilin on the mouse medial vestibular nuclear neurons (MVNs), which play an important role in the control of ocular reflexes. A small number of MVNs, as well as cerebellar floccular Purkinje cells, were labeled with an anti‐motilin receptor antibody. Bath application of motilin (0.1 μm) decreased the discharge frequency of spontaneous action potentials in a group of MVNs in a dose‐dependent manner (Kd, 0.03 μm). The motilin action on spontaneous action potentials was blocked by apamin (100 nm), a blocker of small‐conductance Ca2+‐activated K+ channels. Furthermore, motilin enhanced the amplitudes of inhibitory postsynaptic currents (IPSCs) and miniature IPSCs, but did not affect the frequencies of miniature IPSCs. Intracellular application of pertussis toxin (PTx) (0.5 μg/μL) or guanosine triphosphate‐γ‐S (1 mm) depressed the motilin actions on both action potentials and IPSCs. Only 30% of MVNs examined on slices obtained from wild‐type mice, but none of the GABAergic MVNs that were studied on slices obtained from vesicular γ‐aminobutyric acid transporter‐Venus transgenic mice, showed such a motilin response on action potentials and IPSCs. These findings suggest that motilin could modulate small‐conductance Ca2+‐activated K+ channels and postsynaptic γ‐aminobutyric acid receptors through heterotrimeric guanosine triphosphate‐binding protein‐coupled receptor in a group of glutamatergic MVNs.